Answer:
x =
![(3+2y)/(5y-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4jhdr39vec5a0xqwzmv4se7iv1rhc7vgmd.png)
Explanation:
Given
y =
← multiply both sides by (5x - 2)
y(5x - 2) = 2x + 3 ← distribute left side
5xy - 2y = 2x + 3 ( add 2y to both sides )
5xy = 2x + 3 + 2y ( subtract 2x from both sides )
5xy - 2x = 3 + 2y ( factor out x from each term on the left side )
x(5y - 2) = 3 + 2y ← divide both sides by (5y - 2)
x =
![(3+2y)/(5y-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4jhdr39vec5a0xqwzmv4se7iv1rhc7vgmd.png)